When is switching warranted among biologic therapies in rheumatoid arthritis?. (June 2012) - Reynolds, Alan; Koenig, Andrew S; Bananis, Eustratios; Singh, Amitabh
Switching among biologic therapies is common practice in patients with rheumatoid arthritis who have an inadequate response or intolerable adverse events. Evidence from observational studies and association guidelines supports the use of sequential biologic therapy for these reasons. Owing to recent economic pressures on healthcare budgets, patients with rheumatoid arthritis who are well controlled on and tolerant of their current biologic therapy may be switched to alternative biologics, despite limited evidence supporting this practice. Clinical research and experience suggest that TNF antagonists are not interchangeable, as meaningful differences have been observed in their efficacy and safety profiles. Additional research is needed to assess the risk:benefit ratio of specific sequences of biologic therapies and the validity of switching biologic therapies for nonclinical purposes.